Pengaruh Pendekatan Parenting Style terhadap Motivasi Belajar Siswa Kelas V pada Pembelajaran PKN di UPT SPF SDN Kaccia Kecamatan Tamalate Kota Makassar - Nur Sakina; Suardi Suardi; Musdalifah Syahrir (Departement of Mathematics Education, 2024)
The problem in this research is how the parenting style approach influences the learning motivation of class V students in PKN learning at UPT SPF SDN Kaccia, Tamalate District, Makassar City. This research aims to find out and describe the influence of parenting style on the learning motivation of class V students in PKN learning at UPT SPF SDN Kaccia, Tamalate District, Makassar City. The type of research used in this research is mixed methods. Based on the research results, it shows that there is an influence between parenting style and learning motivation obtained from the completed questionnaire. This can be seen from the simple linear regression equation, namely Y 56.99 + 0.433, meaning that every increase in the regression coefficient X 0.433 illustrates that every 1% increase in parenting style will cause an increase of 0.433 in student learning motivation. That 5 out of 10 parents apply a parenting pattern between authoritarian and democratic or situational parenting. Meanwhile, the rest use a permissive parenting style in the sense of not providing too much support and implementing low levels of control over the child. Based on the results of the research above, it can be concluded that there is a positive influence of parenting style on the learning motivation of class V students in PKN learning at UPT SPF SDN Kaccia, Tamalate District, Makassar City.